Improved pastures and supplementary feeding on the reproductive perfomance of the first calf heifers. - Cachapuz, José Mauro da Silva; Lobato, José Fernando Piva; Leboute, Ema Magalhães (Pesquisa Agropecuaria Brasileira, 2014)
In Dom Pedrito, RS, Brazil, the reproductive performance of the first calf Hereford heifers and the liveweight of the heifers and of their calves were studied at the following conditions: T-I: Natural pasture plus supplementary feeding to supply 60% of the NDT requirements and 100% of the protein requirements as recommended by N.R.C., during a pre-calving medium period of 71 days, and 67 days post-calving; T-II: Natural pasture plus supplementary feeding to supply 60% of the NDT requirements and 65% of the protein requirements, as recommended by N.R.C.; T-III: Improved pasture compound by white dover (Trfolium repens L. var. giganteum Logr.), birdsfoot trefoil (Lotus corniculatus L) and annual ryegrass (Lolium multiflorum L.); T-IV: Natural pasture without supplements during all experimental period. The heifers of the T-I obtained the highest pregnancy rate. These heifers had the highest total liveweight gain, during the pre and post-calving and their calves had higher liveweights at birth and weaning. The heifers of T-II obtained higher pregnancy rate than heifers of T-III, and these ones, higher than heifers of T-IV, as well as the total medium daily liveweight gain, during the pre-calving period and the birth weight of their calves. The calves from T-IV had a higher liveweight at weaning than the calves from T-III.